The Emotional Maturity and Career Decision-Making with Quarter-Life Crisis Among Sumba Students - Putut, Alfredo; Damayanti (Psikodinamika: Jurnal Literasi Psikologi, 2026)
This study aims to examine the influence of emotional maturity and career decision-making on the quarter-life crisis among Sumbanese students pursuing higher education in Malang City. The research employed a quantitative method with a multiple linear regression approach. The population consisted of 248 students enrolled in education as well as history and sociology study programs at private universities in Malang City. A total of 125 respondents were selected using purposive sampling. Data were collected using three instruments: the Emotional Maturity Scale, the Career Decision-Making Scale, and the Quarter-Life Crisis Scale. The analysis results revealed that emotional maturity and career decision-making significantly influence the quarter-life crisis, both partially and simultaneously. These findings indicate that higher levels of emotional maturity and career decision-making ability are associated with lower levels of quarter-life crisis among students. This research is expected to serve as a reference for students, educators, and counselors in assisting individuals to navigate the quarter-life crisis phase more adaptively